2021
DOI: 10.1248/bpb.b21-00231
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of Rasal2 Promotes Non-small Cell Lung Cancer Metastasis through Ras/ERK Pathway

Abstract: The RAS protein activator like 2 (Rasal2) has been reported to be a tumor suppressor in variety of cancers; while an oncogenic protein in ovarian cancer and triple negative breast cancer (TNBC). However, the exact role of Rasal2 in non-small cell lung cancer (NSCLC) is lacking. This study aimed to investigate the role of Rasal2 in NSCLC and the underlying mechanisms. Rasal2 expression level was measured in NSCLC tissue and cells by using quantitative (q)-PCR and immunoblotting analysis. The clinical implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…In lung cancer, previous studies seem to indicate that RASAL2 is a tumor suppressor (Xiong et al, 2021). Low expression of RASAL2 can promote EMT in lung cancer (Li & Li, 2014) and promote metastasis through the RAS /ERK pathway (Fan et al, 2021), which is inconsistent with our results. Our evidence suggests that RASAL2 is a contributing factor to poor prognosis in lung adenocarcinoma.…”
Section: Discussioncontrasting
confidence: 97%
“…In lung cancer, previous studies seem to indicate that RASAL2 is a tumor suppressor (Xiong et al, 2021). Low expression of RASAL2 can promote EMT in lung cancer (Li & Li, 2014) and promote metastasis through the RAS /ERK pathway (Fan et al, 2021), which is inconsistent with our results. Our evidence suggests that RASAL2 is a contributing factor to poor prognosis in lung adenocarcinoma.…”
Section: Discussioncontrasting
confidence: 97%
“…further demonstrated that in cholangiocarcinoma cells, Tspan1 can drive the EMT process through interactions with integrin α6β1 and the consequent amplification of downstream signaling ( 31 ). The Ras-ERK pathway and associated downstream factors are closely tied to the EMT ( 50 , 51 ). Interactions between Tspan9 and integrin β1 may thus strongly impact the ability of OS cells to proliferate and metastasize by shaping intracellular signaling activity.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the RAS/RAF1 pathway stimulates nuclear factor activation signaling and cell protection by regulating scatter factors, which contribute to chemotherapy and radiation resistance 43 . Activation of the RAS/ERK signaling pathway by knocking down RAS protein activator like two can significantly increase the invasion and migration of nonsmall cell lung cancer cells 44 . Under high‐glucose and high‐insulin conditions, RAS/RAF1 protein expression significantly increases, thus promoting MCF‐7 cell proliferation and invasion 45 .…”
Section: Discussionmentioning
confidence: 99%
“…43 Activation of the RAS/ERK signaling pathway by knocking down RAS protein activator like two can significantly increase the invasion and migration of nonsmall cell lung cancer cells. 44 Under high-glucose and high-insulin conditions, RAS/RAF1 protein expression significantly increases, thus promoting MCF-7 cell proliferation and invasion. 45 Therefore, inhibition of the RAS/RAF1 pathway is a promising strategy for addressing PTX resistance and suppressing the development of BC.…”
Section: Author Contributionsmentioning
confidence: 99%